2020
DOI: 10.3390/ijerph17217908
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns during Pregnancy and Their Association with Gestational Weight Gain and Nutrient Adequacy

Abstract: Several epidemiologic studies have shown an association between Gestational Weight Gain (GWG) and offspring complications. The GWG is directly linked to maternal dietary intake and women’s nutritional status during pregnancy. The aim of this study was (1) to assess, in a sample of Spanish pregnant women, the association between maternal dietary patterns and GWG and (2) to assess maternal dietary patterns and nutrient adequate intake according to GWG. A retrospective study was conducted in a sample of 503 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…In line with these findings, the study conducted by Suliga et al 6 showed that in women with excessive GWG, a lower adherence to the prudent pattern was noted in comparison with other participants in the study. The prudent pattern found in this study (high intake of whole grains, vegetables, legumes, sea fish, milk, and dairy products, and avoiding snacking between meals) is similar in terms of composition to the traditional pattern described by Wrottesley et al 22 In addition, Cano-Ibáñez et al 21 found moderate evidence for an association between the Mediterranean eating pattern, considered a healthy eating pattern (vegetables, olive oil, whole grains, and nuts) and lower GWG trajectories (0.06; 95%CI: -0.11--0.04) and better nutrient adequacy.…”
Section: Chart 1 Features Of Articles Included In the Systematic Reviewsupporting
confidence: 84%
See 1 more Smart Citation
“…In line with these findings, the study conducted by Suliga et al 6 showed that in women with excessive GWG, a lower adherence to the prudent pattern was noted in comparison with other participants in the study. The prudent pattern found in this study (high intake of whole grains, vegetables, legumes, sea fish, milk, and dairy products, and avoiding snacking between meals) is similar in terms of composition to the traditional pattern described by Wrottesley et al 22 In addition, Cano-Ibáñez et al 21 found moderate evidence for an association between the Mediterranean eating pattern, considered a healthy eating pattern (vegetables, olive oil, whole grains, and nuts) and lower GWG trajectories (0.06; 95%CI: -0.11--0.04) and better nutrient adequacy.…”
Section: Chart 1 Features Of Articles Included In the Systematic Reviewsupporting
confidence: 84%
“…Dietary patterns are not exactly the same in studies; however, it is clear from published studies that certain dietary patterns like western/unhealthy, healthy/prudent/ Mediterranean, and traditional are often found. 24 The assessed studies were similar in the association of dietary patterns that shows higher caloric density 12,18,19,22,24 with greater chances of excessive GWG outcomes, as well as patterns presenting healthier and more traditional components 6,21,22 being associated with lower GWG.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental research in animal models also showed that maternal high-fat diet (HF) during pregnancy and lactation predisposed offspring to metabolic disorders ( Zheng et al, 2014 ; Ribaroff et al, 2017 ). To reduce the burden of chronic disease in the next generation, management of maternal nutrient supplementation during pregnancy has been discovered to improve perinatal and offspring outcomes ( Mathews et al, 2001 ; Cano-Ibanez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies described an inverse association among GWG [ 141 ] and GDM [ 142 ] related to MedDiet, whereas adequacy of vitamins (B9, D, and E) and dietary fibre were related to the adherence to MedDiet during pregnancy [ 143 ]. GWG seems to be related to the intakes of added sugar, but not to saturated fat or protein.…”
Section: Mediterranean Diet For Prevention Of Obesity and Gestatiomentioning
confidence: 99%